STUDI HERMENEUTIK AL QUR’AN FENOMENA PINJAMAN ONLINE AKULAKU: MAKNA KEBUTUHAN DALAM TRANSAKSI DIGITAL - Muhammad Haqi Awaludin; Alfina Lailatul Fitriyah; Mazro'atus Sa'adah (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This study explores how the concept of human needs in the Qur’an can be reinterpreted within the phenomenon of digital lending, particularly in relation to the use of the Akulaku platform. The shifting meaning of urgent needs among the public often leads to impulsive and excessive borrowing behavior, which stands in contrast to Qur’anic ethical principles. The aim of this research is to reinterpret the meaning of needs using a Qur’anic hermeneutical approach grounded in Gadamer’s theory. This qualitative library study draws on classical and modern Qur’anic exegesis, along with official documents related to digital lending. The analysis employs the hermeneutic circle to connect textual meaning with today’s digital landscape. The findings indicate that the Qur’anic prohibition against excessive consumption applies not only to physical consumption but also to financial consumption in digital forms. The study further shows that digital credit is often used for lifestyle purposes rather than genuine necessity, resulting in financial and psychological strain that conflicts with Islamic legal ethics. Overall, the research argues that legitimate needs in the Islamic tradition should be understood objectively as needs that safeguard human well-being, protect wealth, and uphold moral balance.